2014
DOI: 10.1007/s00216-013-7599-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly imprinted polymer for selective determination of Δ9-tetrahydrocannabinol and 11-nor-Δ9-tetrahydrocannabinol carboxylic acid using LC-MS/MS in urine and oral fluid

Abstract: The use of molecularly imprinted polymers (MIPs) for solid phase extraction (MISPE) allows a rapid and selective extraction compared with traditional methods. Determination of Δ(9)-tetrahydrocannabinol (THC) and 11-nor-Δ(9)-tetrahydrocannabinol carboxylic acid (THC-COOH) in oral fluid (OF) and urine was performed using homemade MISPEs for sample clean-up and liquid chromatography tandem mass spectrometry (LC-MS/MS). Cylindrical MISPE shaped pills were synthesized using catechin as a mimic template. MISPEs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…Although, most of these research studies reported simultaneous development with other catechins at the same time, that is, no reports of plasma analysis are available for catechin individually. Only one method was reported in urine sample analysis for catechins by Lendoiro et al [44]. In addition, the most important reason for the proposed study is a lack of an available method for brain tissue as well as plasma analysis of catechin hydrate alone.…”
Section: Introductionmentioning
confidence: 99%
“…Although, most of these research studies reported simultaneous development with other catechins at the same time, that is, no reports of plasma analysis are available for catechin individually. Only one method was reported in urine sample analysis for catechins by Lendoiro et al [44]. In addition, the most important reason for the proposed study is a lack of an available method for brain tissue as well as plasma analysis of catechin hydrate alone.…”
Section: Introductionmentioning
confidence: 99%
“…Elution time was given as 6.34 min. Molecularly imprinted polymers were used in another study, where extraction time was more than 65 min [4]. In another study, Kwon et al [31] have developed and validated a liquid chromatography-electrospray ionization-tandem mass spectrometric method (LC-ESI-MS/MS) for the direct determination of THC-COOH and its glucuronide in urine.…”
Section: Confirmation Of the Cedia (+) Results Of The Real Samples Wimentioning
confidence: 99%
“…Despite of the very low concentration of Δ 9 -THC in urine, the maximum psychologic effect lasts for 4-6 h. Δ 9 -THC metabolizes very quickly. Firstly, it is converted to its active metabolite 11-nor-Δ 9 -hydroxy-THC (11-OH-THC) through hydroxylation, and then, it is oxidized to form inactive 11-nor-Δ 9 -carboxy-THC (THC-COOH) which is conjugated with glucuronide, existing in both the free and glucuronide form and mainly excreted in urine [4]. Δ 9 -THC metabolites may be detected in urine for up to 12 days following a single oral dose.…”
Section: Introductionmentioning
confidence: 99%
“…These polymers are obtained by the chemical fixation of functional monomers around a template , resulting in cavities with binding sites, complementary to the template . MIPs have been efficiently used to extract drugs from different samples, like urine , plasma , water , beef liver extracts , soil and hair . Moreover, different SPE approaches have been developed with MIPs.…”
Section: Introductionmentioning
confidence: 99%